2020
DOI: 10.1097/md.0000000000020678
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of Chinese herbal medicine for the treatment of patients with early diabetic nephropathy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…CER was assessed based on the degree of improvement of TCM clinical symptoms before and after treatment. This evaluation criterion was widely used to evaluate the efficacy of TCM (55)(56)(57). Further, the node splitting method showed that the direct and indirect evidence supporting treatment efficacy was consistent.…”
Section: Discussionmentioning
confidence: 99%
“…CER was assessed based on the degree of improvement of TCM clinical symptoms before and after treatment. This evaluation criterion was widely used to evaluate the efficacy of TCM (55)(56)(57). Further, the node splitting method showed that the direct and indirect evidence supporting treatment efficacy was consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of CRF by TCM has elicited positive results, however, and this approach has led to a diversi cation of treatment methods, broadening developmental prospects for therapy [17]. To name but a few of the effects, TCM has had impressive achievements in relieving symptoms of CRF, protecting residual renal function, delaying the progress of the disease, and postponing the time of dialysis and the requirement for kidney transplantation, thereby greatly improving the quality of life for patients with CRF [18].…”
Section: Fig 9 Discussionmentioning
confidence: 99%
“…The on-going RCT of Tangshen Formula aims to investigate its effectiveness and safety on treating type 2 DKD patients with macroalbuminuria ( Yan et al, 2016 ). The meta-analysis of RCTs shows the satisfied efficacy of combined Tripterygium wilfordii Hook, tripterygium glycosides, Ophiocordyceps sinensis, or Jinshuibao with conventional ACEI or ARB treatment against DKD ( Luo et al, 2015 ; Lu et al, 2018 ; Zhang et al, 2019b ; Ren et al, 2019 ; Wu et al, 2020 ; Yang et al, 2020 ).…”
Section: Clinical Application Of Chinese Herbal Medicine In Diabetic ...mentioning
confidence: 99%